Ethical leadership in organizations : concepts and implementation - Bachmann, Bernhard (Springer, 2017)
This book links ethical leadership theory to the implementation of improved leadership practices, particularly in highly operational environments. It builds on the recognition that bad forms of leadership lead to declining motivation and consequently to problems in the social climate and quality of work in organizations and the personal health of employees. It is based on a qualitative study from 100 in-depth interviews using inductive categorization, retrieving deep, rich and unprompted data from a highly developed and advanced production facility. The book reviews the current state of research in this field and describes the setup of the underlying study, linking it to the author's professional experience. It discusses the research design, its testing and its adaption to organizational practice. The book presents the findings of the study, introduces specific issues arising from the analysis, then critically discusses the interpretation of the findings and matches these with theoretical concepts. One finding of the study is that CSR and ethics are too often implemented with a focus on governance, process and reporting, without looking at leadership on all levels as the critical component. Finally it discusses the conclusions and implications derived from the findings. Overall, the book critically assesses how ethical leadership can be practically implemented in business organizations as a means of transforming organizations into better-governed institutions that exhibit ethical behavior.
Keywords: Leadership -- Moral and ethical aspects.; Business ethics.; Social responsibility of business.; Industrial management -- Moral and ethical aspects.; elektronické knihy; electronic books